2006
DOI: 10.1007/s00192-006-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of foot reflexology for patients with symptomatic idiopathic detrusor overactivity

Abstract: The aim of this study was to examine whether foot reflexology has beneficial effects on patients with idiopathic detrusor overactivity. One hundred and nine women with symptomatic idiopathic detrusor overactivity were randomized into either foot reflexology treatment group or nonspecific foot massage control group. The primary outcome measure was the change in the diurnal micturition frequency. There was significant change in the number of daytime frequency in the reflexology group when compared with the massa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Although no studies were found on the effect of reflexology on urinary frequency, the number of people with urinary frequency at grade 1 or over was found to be lower in the reflexology group according to the present study. Similar to this study, Mak, Cheon, Wong, Liu, and Tong (2007) revealed that the urinary frequency in the day time decreased in the reflexology group of patients with symptomatic idiopathic detrusor activity. This may be because reflexology increased blood flow to the kidneys and bladder and supported muscular tonus.…”
Section: Toxicity Assessmentssupporting
confidence: 89%
“…Although no studies were found on the effect of reflexology on urinary frequency, the number of people with urinary frequency at grade 1 or over was found to be lower in the reflexology group according to the present study. Similar to this study, Mak, Cheon, Wong, Liu, and Tong (2007) revealed that the urinary frequency in the day time decreased in the reflexology group of patients with symptomatic idiopathic detrusor activity. This may be because reflexology increased blood flow to the kidneys and bladder and supported muscular tonus.…”
Section: Toxicity Assessmentssupporting
confidence: 89%
“…Of the clinical trials, 37 were RCTs [15, 2762], 10 were single-arm trials [6372] and six were open-label extension studies [7378]. The clinical trials included eight mirabegron studies [38, 4345, 48, 58, 59, 61], six onabotulinumtoxinA studies [30, 35, 49, 53, 54, 74], 35 antimuscarinic studies [15, 2729, 3134, 36, 37, 3942, 46, 5052, 55, 56, 60, 6273, 75, 76], two sacral nerve modulation studies [77, 78], one staged InterStim procedure study [57] and one study of foot reflexology [47].…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Mak and friends; 54 women who have overactive bladder received reflexology, 43 women received nonspecific foot massage. In groups, 24 hours micturition frequency and urgency incontinence, incontinence complaints were decreased and in terms of 24 hours micturition frequency, it was determined that reflexology is more effective than the foot massage [8]. In the randomize controlled study of SievNer and friends; reflexology was applied to Multiple Skleroz patients and in the group that received reflexology, it was determined that urinary symptoms decreased significantly [7], again in Hughes and friends study which was conducted with Multiple Skleroz patients, reflexology and placebo foot massage were applied to patients for ten weeks and in the evaluation results, it was determined that there was 33% improvement in muscular spasm and urgency symptoms [19].…”
Section: Resultsmentioning
confidence: 99%
“…When the effect of reflexology on overactive bladder examined, massage that applied on kidney and bladder with target organ effect, it increases perfusion and lowers muscle power and tonus, consequently, improvement on urinary symptoms was determined [7,8].Because of its effects which can be harmful has not been reported in the literature, it was stated that reflexology can be used as a non-invasive procedure in treatment of OABS which is a multidimensional problem. Therefore, this study was conducted to determine the effectiveness of reflexology in women with OABS.…”
Section: Introductionmentioning
confidence: 99%